PENERAPAN METODE EXTREME PROGRAMMING PADA PENGEMBANGAN SISTEM INFORMASI EVALUASI HAFALAN AL-QUR’AN - Dian Riskiyana; Dwi Sakethi; Rico Andrian (Jurnal Pepadun, 2021)
Monitoring refers to the process of gathering and analyzing information that is systematic and continuous related in improving the program. The Al-Qur’an memorization monitoring system that has been running is systematic, but not yet efficient. Recording memorization that uses conventional method requires a great deal of time to recap memorization. This research aimed to develop a system that can act as a medium for recording and monitoring the Al-Qur’an memorization. This research used the Extreme Programming method. This research result is the development of web based the Al-Qur’an memorization monitoring system with unit testing and acceptance testing that suit the needs of users. The Al-Qur’an memorization monitoring system can see memorization recap, record memorization, see memorized surah and see memorization chart. The Al-Qur’an memorization monitoring system can evaluation in the memorized Al-Qur’an.